2007
DOI: 10.1038/sj.onc.1210556
|View full text |Cite
|
Sign up to set email alerts
|

Significance of HIF-1-active cells in angiogenesis and radioresistance

Abstract: Human solid tumors contain hypoxic regions that have considerably lower oxygen tension than the normal tissues. Hypoxia offers resistance to radiotherapy and anticancer chemotherapy, as well as predispose to increased tumor metastases. Furthermore, hypoxia induces hypoxia-inducible factor-1 (HIF-1), which in turn increases tumor angiogenesis. Thus, eradication of HIF-1-active/hypoxic tumor cells is very important for cancer therapy. We have previously reported that procaspase-3 fused with a von Hippel-Lindau (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 29 publications
2
111
0
1
Order By: Relevance
“…For diaminobenzidine staining of pimonidazole hydrochloride and CD31, the formalin-fixed and paraffinembedded sections were treated with anti-pimonidazole antibody and anti-CD31 antibody respectively, as described earlier (Harada et al, 2007a;Liu et al, 2007;Zeng et al, 2008). For fluorescent double staining of HIF-1a and pimonidazole, the tumour xenografts were embedded in OCT compound and frozen at À801C.…”
Section: Immunohistochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…For diaminobenzidine staining of pimonidazole hydrochloride and CD31, the formalin-fixed and paraffinembedded sections were treated with anti-pimonidazole antibody and anti-CD31 antibody respectively, as described earlier (Harada et al, 2007a;Liu et al, 2007;Zeng et al, 2008). For fluorescent double staining of HIF-1a and pimonidazole, the tumour xenografts were embedded in OCT compound and frozen at À801C.…”
Section: Immunohistochemical Analysesmentioning
confidence: 99%
“…Indeed, several pre-clinical studies showed that the inhibition of intratumoral HIF-1 activity with an HIF-1 inhibitor, YC-1, significantly enhanced the therapeutic effect of radiation (Moeller et al, 2004). Likewise, the elimination of HIF-1-positive cells from solid tumours with a protein drug, TOP3, or with a gene therapy strategy had radiosensitising effects (Harada et al, 2002(Harada et al, , 2007aLiu et al, 2007). However, the inhibition of intratumoral HIF-1 activity in unsuitable timing may suppress rather than enhance the effect of radiation therapy; in that the inhibition has an anti-angiogenic effect and consequently increases the radioresistant hypoxic fraction (Yeo et al, 2003).…”
mentioning
confidence: 99%
“…As mentioned above, a high SUV is correlated with an inferior overall patient survival (5-7). It has been noted that the tumor microenvironment of many malignancies contains a hypoxic condition, a condition associated with resistance to anticancer agents and poor prognosis (12)(13)(14). Hypoxia-inducible factor-1· (HIF-1·) was found to be upregulated in a broad range of tumors and is involved in angiogenesis, invasion and altered glucose metabolism (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…clinical and experimental evidence suggests that hypoxic processes in cancer cells contribute to the malignant phenotype and to more aggressive tumor behavior (2). Hypoxia offers resistance to anticancer chemotherapy, as well as a predisposition to increased tumor metastases (3). Investigation of the molecular mechanisms specific to cancer cells under hypoxic conditions is important to provide a basis for anticancer therapy.…”
Section: Introductionmentioning
confidence: 99%